Optimization of high purity chitin and chitosan production from Illex argentinus pens by a combination of enzymatic and chemical processes. (15th October 2017) - Vázquez, José Antonio; Noriega, Diana; Ramos, Patricia; Valcarcel, Jesus; Novoa-Carballal, Ramon; Pastrana, Lorenzo; Reis, Rui L.; Pérez-Martín, Ricardo I.
Highlights: Production of chitin and chitosan from Illex argentinus pens was optimised. Optimal conditions for chemical and enzymatic proteolysis of squid pen were defined. Alkaline deacetylation of chitin was subsequently optimized for chitosan production. Best values for chitosan were 61.0–63.7% of NaOH and 14.9–16.4 h of deacetylation. Molecular weights of chitosan ranged from 143 to 339 kDa. Abstract: The present report illustrates the optimisation of the experimental conditions for the chemical and enzymatic production of chitin and chitosan from Illex argentinus pen by-products. Optima conditions for chitin isolation were established at 0.82 M NaOH/36.4 °C, 57.5 °C/pH = 9.29, 59.6 °C/pH = 9.30 and 49.6 °C/pH = 5.91 for chemical, alcalase, esperase and neutrase deproteinization, respectively. Chitin samples were subsequently deacetylated by alkaline treatment reaching the highest degrees of deacetylation (DD > 93%) at 61.0–63.7% of NaOH and 14.9–16.4 h of hydrolysis depending on the type of process previously performed to the squid pens. Molecular weight (as number average molecular weight, Mn) of chitosan produced in the experimental designs ranged from 143 kDa (PDI 2.37) to 339 kDa (PDI 2.38).